Home time (2017), book one ebook Book one. - Whyte, Campbell (Home Time (2017)., 2017)
The last school bell has rung and it's finally HOME TIME! Even though they're twins, Lilly and David don't agree on much... except that the last summer before high school is the perfect time for relaxing with friends. But their plans for sleepovers, fantasy games, and romance are thrown out the window when the whole gang falls into a river and wakes up in a village of fantastic creatures.